Pengaruh Financial Target, Ineffective Monitoring, Pergantian Auditor, dan Perubahan Direksi Terhadap Kecurangan Laporan Keuangan - Revina Resty Utami; Yetty Murni; Widyaningsih Azizah (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2022)
This study aims to determine the effect of financial target, ineffective monitoring, auditors change, and directors change on financial statement fraud which is proxied by earnings management. The proxied of each variables are return on asset (ROA), ratio of independent board of commissioners, and dummy variables for auditor change and director change. The data is secondary data. The population is manufacturing companies sector consumer goods industry listed on Indonesia Stock Exchange (IDX) for the period 2016-2019. The research sample consisted of 28 companies using purposive sampling. Hypothesis testing used multiple linear analysis by using of Eviews10 software application. The results of this study indicate that financial target and auditor change had a significant positive effect on financial statement fraud, while ineffective monitoring and director change had no effect on financial statement fraud.